Expert committee on Malaria: Eighth report - World health organisation (Geneva: World health organisation, 1961)
This volume reports the recommendations and conclusions of an expert committee convened to assess progress in implementation of the Global Malaria Control Strategy, adopted in 1992. It offers advice on a wide range of issues that can aid countries strengthen programs for control.
Introduction -- Review of present status of malaria eradication and prospects for the future -- Evaluation techniques and surveillance in eradication programmes -- Criteria for malaria eradication -- Cycles and dosages of insecticides in eradication programmes -- Approach to malaria eradication in developing countries -- The place of drugs in malaria eradication -- Simian malaria in relation to malaria eradication -- Seventh award of the darling medal and prize -- Recommendations
Keywords: Medical sciences -- Malaria